Tall order: A sociological study on height preferences of selected Filipino youth in heterosexual relationships - Taduran, Richard Jonathan O (2021)
The height of a person has become a topic of increasing interest not only in biological sciences but also in the social sciences. Filipino height has rarely been studied, and height preference in romantic coupling of Filipinos has never been a topic of any research. This study aimed to discern the meaning of height in heterosexual romantic relationships of selected Filipino youth: whether height preferences for the opposite sex matter and if so, what those preferences are and the reasons behind such preferences. Data were collected from 100 students of the University of the Philippines by utilizing open-ended qualitative survey questionnaires. Results show that most female respondents (96%) preferred to date men taller than them. Both females and males believe that height is an important factor in romantic relationships, both citing various reasons such as society, protection, masculinity/femininity, power, and aesthetics. Gender-based explanation of height preferences appear more prominent than evolutionary-based legitimation.